Morphological characterization of ginger (Zingiber officinale) using DUS descriptors - J, AKSHITHA H; K, UMESHA; D, PRASATH (The Indian Journal of Agricultural Sciences, 2019)
Ginger (Zingiber officinale Rosc.) is an important spice crop cultivated for its fresh and dried rhizomes. Ginger never sets seed and sexual recombination has never been reported. Cultivars have evolved by unconscious selection and are generally known by the name of the region. Moreover, it is propagated vegetatively and hence, differentiation of genotypes morphologically is difficult. Twenty-seven ginger genotypes were characterized morphologically using DUS guidelines for eight quantitative and two qualitative characters. Among the characters, four characters were monomorphic, four were dimorphic and two were found to be polymorphic. Grouping of genotypes showed narrow variability for most of the morphological characters whereas, rhizome characters exhibited remarkable variability.